Particle size distribution estimation of a mixture of regular and irregular sized particles using acoustic emissions - Nsugbe, Ejay; Starr, Andrew; Jennions, Ian K.; Ruiz Carcel, Cristobal (Elsevier, 2017)
This works investigates the possibility of using Acoustic Emissions (AE) to estimate the Particle Size Distribution (PSD) of a mixture of particles that comprise of particles of different densities and geometry. The experiments carried out involved the mixture of a set of glass and polyethylene particles that ranged from 150-212 microns and 150-250microns respectively and an experimental rig that allowed the free fall of a continuous stream of particles on a target plate which the AE sensor was placed. By using a time domain based multiple threshold method, it was observed that the PSD of the particles in the mixture could be estimated.
Keywords: Manufacturing improvement; Process optimisation; In-line monitoring; Lean production; Process monitoring; Non-contact measurement; Acoustic emissions; Particle sizing; Particle size distribution